ПОЛЕЗНЫЕ СВОЙСТВА HELIANTHUS ANNUUS L. - Esanov, Husniddin; Aslonova , Kimyo (Центр Научных Публикаций (buxdu.uz), 2021)
The article provides information on the beneficial properties of Helianthus annuus L. varieties, organic matter in it. In particular, its medicinal properties and role in the treatment of diseases.